A rare case of urethral triplication in association with tethered cord and vertebral anomalies. Issue 3 (July 2016) - Kurian, Jujju J.; Homi, Susan Jehangir; Karl, Immanuel S.
Abstract : In this manuscript, we describe the case of a 5-year-old boy with Y triplication of the urethra in association with fatty filum terminale, tethered cord and vertebral anomalies. Unlike a Y duplication in which the penile meatus is hypoplastic, a Y triplication can have a penile meatus of adequate calibre, which can be used as a functional conduit. Most patients with urethral triplication have been found to have associated malformations. To our knowledge, this is the first reported case of urethral triplication seen in association with fatty filum terminale, tethered cord and vertebral anomalies.